Age-related disparities in heart failure: insights into clinical profiles, treatment gaps, and outcomes from a multi-center and multi-ethnic study - A.Z. Y., Koh; B. K., Chung; Hwei Sung, Ling; C. Z. F., Chua; W. K., Ho; K. C., Cheah; S. L., Kwa; J., Namasoo; C. H., Chai; P. W., Ting; M. J., Khaw; J. K. W., Wong; et al. (European Society of Cardiology, 2025)
Background: Heart failure (HF) is a significant cause of morbidity and mortality. Differences in clinical characteristics and treatment outcomes between elderly and younger patients remain underexplored. Purpose: To evaluate disparities in demographics, comorbidities, prescription of guideline-directed medical therapy (GDMT), and clinical outcomes in elderly versus younger HFrEF patients. Methods: A retrospective, multi-center cohort study analyzed 578 HF patients who attend dedicated HF clinics in ten hospitals between January 1, 2021, and June 30, 2023, categorized into elderly (≥65 years, n=176) and younger (<65 years, n=402) groups. Data included demographics, comorbidities, EF, New York Heart Association (NYHA) functional class, GDMT prescription at baseline, 3 months, and 6 months, and clinical outcomes, including hospitalizations and mortality. Results: Elderly HF patients demonstrated notable differences compared to younger patients in several demographic, clinical, and outcome measures. They had a higher proportion of females (34.7% vs. 19.2%, p<0.001) and exhibited a greater prevalence of comorbidities, including hypertension (76.6% vs. 63.9%, p=0.003), diabetes (47.4% vs. 36.8%, p=0.017), dyslipidemia (63.6% vs. 48.3%, p<0.001), atrial fibrillation (36.2% vs. 17.5%, p<0.001), chronic kidney disease (41.9% vs. 21.2%, p<0.001), and anemia (39.4% vs. 22%, p<0.001). Regarding cardiac function, elderly patients had a higher proportion of EF > 40% (16.1% vs. 9.8%, p=0.007), with 6.9% having EF 41-49% and 9.2% EF ≥ 50%, compared to 6.8% and 3%, respectively, in younger patients. Baseline EF was significantly lower in younger patients (32.4±12.4% vs. 28.1±9.9%, p=0.041), though both groups showed comparable improvements over six months. In terms of guideline-directed medical therapy (GDMT), elderly patients achieving lower RAAS inhibitor prescriptions at three months (81% vs. 88.1%, p=0.034). Elderly patients had fewer 3-pillars and 4-pillars GDMT than younger patients at three months (74.5% vs. 84.0%, p=0.044) and 6 months (75.1% vs. 86.0%, p=0.005). Outcomes revealed that elderly patients had higher six-month mortality rates (12.7% vs. 5.9%, p=0.007), although heart failure hospitalization rates were similar between the groups (6.2% vs. 9.1%, p=0.219). Conclusion: Elderly HF patients face greater challenges in managing comorbidities and achieving optimal GDMT prescription, contributing to higher mortality rates. Tailored interventions are needed to improve outcomes in this high-risk population.